Extended curriculum programme students’ attitude towards English as a second language in a South African university - Megbowon, Funmilola Kemi; Uwah, Chijioke (Penerbit Universiti Kebangsaan Malaysia, 2023)
English is one of the top ten international languages spoken by people globally and it has continued to play a dominant role in various fields and sectors. Despite the importance of English, it has been a subject of political and social debate in the South Africa space. Nevertheless, irrespective of arguments for and against it, English remains an indispensable language to learn and understand for any globally oriented people, institution, and country. Attitude towards a foreign language learning are part of factors that influence success or otherwise in such a language learning process. Thus, this study aims to investigate the attitude of ECP students towards English and English language learning. The study further explores the differences in the attitudes of ECP students by gender. The participants of the study were a sample of 98 students who were selected through a simple random sampling of students from two different academic years of the ECP in the Faculty of Management and Commerce. Descriptive and inferential analytical techniques were applied on information obtained through a closed-ended questionnaire. The study found that respondents have a positive attitude towards English and English Learning. Therefore, this study concludes that social and political debates on language policies in higher institutions of learning should not be done outside the perception and realities of direct receivers of socio-political debate outcomes. Furthermore, strategies to enhance the English language skills of the students in the midst of the eleven recognized national languages that cannot be absolutely accommodated in the South African higher institutions of learning should be continually developed.